Hygiene risk assessment health problems of women working in metallurgical production - Iesmanchuk, I. N.; Єсманчук, І. М. (г. Шымкент: Серпилис, 2016)
Now medical and demographic situation has deteriorated, and the problem of the influence of harmful factors of production increased. Our priority is a member of the women's health study in this area. According to the World Health Organization, the incidence of infertile marriages is on average 10-15% in different populations and in 40-50% due to a violation of female infertility. Currently, we examined the effects of bad metallurgical production on women's health. In the analysis of the scientific literature show that such factors affect the body of women: hot microclimate, electromagnetic field, industrial noise, vibration. The purpose of the researching. Тo determine the effect of the metallurgical plant on women's health.
Keywords: тези